Case study: student's satisfaction level towards UiTM Sarawak Library's services / Noorziah Bigu, Nurul Ain Yaakub & Frida Jarah David - Bigu, Noorziah; Yaakub, Nurul Ain; David, Frida Jarah (2010)
This paper reports a part of a quantitative study that aims to evaluate the library’s performance by measuring the users’ satisfaction with library services, infrastructure or place or space and collection or information provided by an academic library in UiTM, Sarawak. A self-developed questionnaire was used to gauge the respondents’ opinions on their satisfaction level on the statements regarding the dimensions. The instrument was distributed to a sample of 100 students from differences faculties and also difference gender of the university. The results of the study revealed that the respondents were only quite satisfied with the library services, infrastructure or place or space, and collection or information of the library as a whole. The results also showed significant differences on the satisfaction on services, infrastructure or place or space, and libraries’ collection or information among the respondents.